A Sustainability Index for Evaluating Vegetation Restoration Under Rainwater Resources Limitation - Wenjing Yang; Yong Zhao; Jianshi Zhao; Huanyu Chang (Geophysical Research Letters)
Abstract Evaluating vegetation restoration sustainability is crucial to avoid conflicts between human water demand and ecosystem consumption, especially with the surge in leaf area index (LAI) due to revegetation projects in China. However, current methods for assessing vegetation sustainability are still limited. Here, we developed a sustainability index for vegetation systems (vegetation sustainability index, VSI) from water demand and supply aspects based on reliability, resilience, and vulnerability in arid and semi‐arid areas. VSI was built upon a vegetation overplanting index (dLAI) which is the difference between the maximum LAI supported by precipitation (LAIp) and the observed LAI (LAIobs). A case study in the mountainous area of the Haihe River basin reveals gradually declining VSI after 2000. Forests are the primary vegetation type in areas with VSI < 0.5, indicating decreased sustainability due to overplanting. The framework of VSI can be a useful tool for planning and implementing vegetation restoration strategies in arid and semi‐arid regions.